Multipoint visualization of ULF oscillations using the Super Dual Auroral Radar Network. Issue 18 (23rd September 2014) - Bland, Emma C.; McDonald, Andrew J.; Menk, Frederick W.; Devlin, John C.
Abstract We present a technique for the automatic detection of Pc5 (150 s to 600 s period) ultralow frequency (ULF) pulsations in ground and ionospheric backscatter from the Super Dual Auroral Radar Network (SuperDARN). This new technique enables rapid identification and visualization of ULF oscillations over the very wide geographical coverage of SuperDARN. The technique detects ULF oscillations using the Lomb‐Scargle periodogram method, which provides a natural test for periodic behavior against the null hypothesis of a pure noise distribution. This does not require any interpolation across data gaps and is thus appropriate for SuperDARN data. We demonstrate the application of the technique to SuperDARN data for March 2014 and find that Pc5 pulsations are frequently observed by multiple radars simultaneously. A preliminary investigation using data from all Northern Hemisphere SuperDARN radars indicates that Pc5 pulsation activity occurs most often on the nightside of the magnetosphere, with a mean frequency of about 2 mHz.